FOSTERING STUDENTS’ UNDERSTANDING OF LE CHATELIER’S PRINCIPLE USING CORRECTIVE FEEDBACK INSTRUCTIONAL STRATEGY - Opateye, Johnson Ayodele (Sokoto Educational Review, 2012)
The paper examined the use of corrective feedback as an instructional strategy to foster understanding of Le Chatelier’s principle among secondary school chemistry students. Le Chatelier’s principle which focuses on chemical reactants and products in chemical equilibrium confirms that the reaction system tends to counteract the effect of any variation in the variables to maintain the equilibrium as in SSS chemistry curriculum. The principle needs to be understood and applied by all chemistry students. It views classroom questioning as a base for effective feedback and correctives and provided a checklist for planning such questions. The inability of chemistry teachers to involve students in classroom discussions, delay feedback and ineffective mode of classroom interaction among learners constitute a hindrance to students understanding of Le Chatelier’s principle. Application o f corrective feedback as a strategy fo r classroom chemistry instruction to teach Le Chatelier’s principle was therefore illustrated. Corrective feedback assisted the students to have a deeper understanding of Le Chatelier’s principle and also enhanced their participation when discussing this concept in the class as active learners. Chemistry teachers could apply active learning interaction through corrective feedback strategy to improve students’ understanding of Le Chatelier’s principle. Students’ responses to questions should be given immediate feedback to remove conceptual confusion during the course o f lesson.